The Influence of Product Quality, Brand Image and Promotion on Product Repurchase Interest - Syahzad, Amir; Rizal, Tengku; Agustinus, Aberto (International Journal of Applied Management and Business, 2026)
This study aim to determine the effect of Product Quality, Brand Image and Promotion on Repurchase Interest on products  mediated by Consumer Loyalty. The subjects in this study were consumers who already had more than one sandal shoe product . The sample used in this study was 200 respondents. The sampling technique used purposive sampling. Researchers used questionnaires to collect data. The data analysis technique used in this study was The Structural Equation Modeling (SEM) using PLS 4.0 statistical software. based on the research results obtained that Product quality does not have a significant effect on consumer loyalty, Brand image has a positive and significant effect on consumer loyalty, Promotion does not have a significant effect on consumer loyalty, Consumer loyalty has a positive and significant effect on repurchase interest, Product quality has a positive and significant effect on repurchase interest, Brand image has a positive and significant effect on Repurchase interest, Promotion has a positive and significant effect on repurchase, Consumer loyalty mediates the relationship between Product Quality and Repurchase Interest, Consumer Loyalty is unable to mediate the effect of Brand Image on Repurchase Interest, Consumer Loyalty is unable to mediate the effect of promotion on Repurchase Interest.